DNA hybridization mechanism in an interfacial environment: What hides beneath first order k (s(-1)) kinetic constant? - Lazerges, M.; Perrot, H.; Rabehagasoa, N.; Compere, C.; Dreanno, C.; Mucio Pedroso, M.; Faria, R. C.; Bueno, Paulo Roberto [UNESP] (Elsevier B.V. Sa, 2012)
The scientific question addressed in this work is: what hides beneath first order kinetic constant k (s(-1)) measured for hybridization of a DNA target on a biosensor surface. Kinetics hybridization curves were established with a 27 MHz quartz microbalance (9 MHz, third harmonic) biosensor, constituted of a 20-base probe monolayer deposited on a gold covered quartz surface. Kinetics analysis, by a known two-step adsorption-hybridization mechanism, is well appropriate to fit properly hybridization kinetics curves, for complementary 20-base to 40-base targets over two concentration decades. It was found that the K-1 (M-1) adsorption constant, relevant to the first step, concerns an equilibrium between non hybridized targets and hybridized pre-complex and increases with DNA target length. It was established that k(2) (s(-1)), relevant to irreversible formation of a stable duplex, varies in an opposite way to K-1 with DNA target length. (C) 2012 Published by Elsevier B.V.
Keywords: Biosensors; DNA; Hybridization kinetics; Quartz crystal microbalance